THE INCOMPLETE PROCESS OF INDONESIAS DEMOCRATIZATION - Paskal Kleden (Kedeputian Bidang Ilmu Sosial dan Kemanusiaan (IPSK-LIPI), 2011)
The two editors of the book, Edward Aspinall and Marcus Mietzner havebeen actively researching Indonesian politics since their adolescence.Aspinall lived previously for several years in Malang and Mietznerconducted his initial research on Indonesia in Ambon. The two editors,now scholars at the Australian National University in Canberra, belongto the new generation of Indonesian experts.The two Australia based scholars represent a shift from the dominanceof the American based experts from the earlier generation such asGeorge McTurnan Kahin (Cornell University), Benedict Anderson(Cornell University), and Daniel S. Lev (Washington University), whoresearched Indonesia during the Cold War period. At that time Indonesiawas considered as a country threatened by the domino effects ofcommunism that already swept China, North Korea, Vietnam, Laos,and Cambodia, leading to increased funds for Indonesian studies in theUS, and therefore contributing to in depth political analysis producedamong others by the Cornell Modern Indonesia Project (CMIP).However, the importance of Indonesia in particular and Asian studiesin general (Ellings & Hathaway 2010: 2) abated in the post Cold Warperiod as attention is drawn further to more severe con?ict areas.Therefore, with this book the two editors aim at bringing Indonesiaback to the international political discourse. They argue that most ofthe comparativists, for instance like the Washington DC based Freedomhouse, have treated Indonesia only as one country among many others212 | Masyarakat Indonesiain their quantitative analyses. A number of important work on Indonesiahave also been published by junior scholars, unfortunately they lackin?uence for triggering a larger international debate on Indonesia.